2016
DOI: 10.1177/1079063216667921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sex Offenders With the Minnesota Multiphasic Personality /Inventory–2–Restructured Form

Abstract: This study examined the association between scores on the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF) with static and dynamic risk assessment instruments, including the STATIC-99 and Level of Service Inventory-Revised (LSI-R). The sample included 304 male adults who were convicted of sexual offenses against children and were referred to a sex offender treatment program. On average, the sample had a Low-Moderate risk of re-offending according to the STATIC-99 and LSI-R. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The present study represents the first step toward identifying risk factors associated with sexual offending among clergy applicants with the MMPI-2-RF. The MMPI-2-RF was not created to identify sexual offenders of minors but has been recently retroactively mapped onto known risk factors (Tarescavage et al, 2018). The MMPI-2-RF profiles of sexual offenders look "normal"; that is, no scores above the cut-off of T ϭ 65.…”
Section: Discussionmentioning
confidence: 99%
“…The present study represents the first step toward identifying risk factors associated with sexual offending among clergy applicants with the MMPI-2-RF. The MMPI-2-RF was not created to identify sexual offenders of minors but has been recently retroactively mapped onto known risk factors (Tarescavage et al, 2018). The MMPI-2-RF profiles of sexual offenders look "normal"; that is, no scores above the cut-off of T ϭ 65.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond improved validity, another way that the MMPI-2-RF has helped to address some historical criticisms of the MMPI-2 is in research on sexual offender recidivism assessment. Exemplifying this contribution, research has found that the MMPI-2-RF scales are informative during evaluations of convicted child sexual offenders with associations between specific MMPI-2-RF scales and scores on known risk assessment instruments (STATIC-99 and Level of Service Inventory—Revised; Tarescavage, Cappo, & Ben-Porath, 2018). Specifically, the MMPI-2-RF scales measuring Juvenile Conduct Problems (JCP), Substance Use (SUB), Family Problems (FML), Social Avoidance (SAV), Disaffiliativeness (DSF), Disconstraint (DISC-r), Behavioral Dysfunction (BXD), Cynicism (RC3), Antisocial Behavior (RC4), Persecutory Ideation (RC6), Impression Management (L-r), and Underreporting (K-r) mapped onto dynamic risk factors of sexual offending including resistance to rules, hostility, emotional deficits, impulsivity, and lack of intimate adult relationships.…”
Section: Mmpi-2 and Mmpi-2-rf Testing Of Clergy Applicantsmentioning
confidence: 99%
“…Despite these strengths, we are aware of only one study that has utilized the MMPI-2-RF with clergy applicants (Isacco et al, 2019). That study compared mean scores of clergy applicants with the sexual offender sample on 12 MMPI-2-RF scales consistent with sexual offending risk factors (see Tarescavage et al, 2018). In general, diaconate and seminary applicants scored significantly lower than the normed sample of sexual offenders across risk factors, with the exception of the impression management and defensiveness scales (i.e., L-r and K-r).…”
Section: Mmpi-2 and Mmpi-2-rf Testing Of Clergy Applicantsmentioning
confidence: 99%
“…On the other hand, studies using the PAI (Morey, 1991) to assess sexual offenders point towards some potential predictive ability of this tool (especially the antisocial scale) for recidivism outcomes among sex offenders (Boccaccini, Murrie, Hawes, Simpler, & Johnson, 2010;Jung et al, 2018); although it did not improve the validity of tailored measures for sexual recidivism risk assessment (Jung et al, 2018). With regard to the MMPI-2-RF (Ben-Porath & Tellegen, 2011), measures of externalizing dysfunction among sexual offenders with child victims showed the strongest associations with static and dynamic risk tools for sexual reoffending assessment (Tarescavage, Cappo, & Ben-Porath, 2018).…”
Section: Introductionmentioning
confidence: 99%